Lumped parameter modelling for the thermal analysis of the launch vehicle Vega C. Issue 3 (9th April 2018) - Olivero, Mattia; Ferrai, Matteo; Pantaleone, Piero; Perkovic, Ivan; D'Amato, Antonella; Moroni, David; Perugini, Pierluigi; Tirelli, Matteo
Abstract : Purpose: This activity dealt with the thermal analysis of the launch vehicle Vega C through a lumped parameter model. The Vega C is the upgrade of the actual launch vehicle Vega within the Vega Consolidation and Evolution Program, whose objective is to develop a consolidated – hence the C – version of the Vega by 2020. The main aim of the study was verifying the thickness of the external thermal protection of the launch vehicle, such that the structure and equipment temperatures were kept within their operating ranges. Design/methodology/approach: The analysis has been performed by means of ESATAN–TMS during a time-frame that included the stand-by on ground phase and a flight phase up to the separation of the second stage from the third one. Two operating conditions have been considered, i.e. the worst hot and worst cold cases. The study has been divided as follows: geometry definition through spatial discretization; application of materials and optical properties; application of thermal loads; thermal analysis; and post-processing of the results in ThermNV . Findings: It was concluded that the calculated temperatures were within the supposed project specifications, while their trends reflected the expected behavior. Originality/value: During the flight phase, the mutual separation of the investigated stages has been explicitly modelled through a routine specifically developed for this purpose. Therefore, the submodels of each stage have been disabled at the correct instant according to the known time-sheet.